Tingkat Kecemasan Anak terhadap Pelayanan Kesehatan Gigi di Poli Gigi Puskesmas - Jumriani; Liasari, Ira; Devi, Sri; Widyastuti, Nugraheni (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2023)
One of the key factors contributing to the failure of dental healthcare services is the presence of anxiety and tension in patients, particularly pediatric patients. As a result, preventive measures or further treatment may need to be postponed until the next visit. This study aimed to investigate the level of anxiety among children receiving dental healthcare services at Puskesmas Palangga based on age, gender, and type of dental healthcare service. A descriptive research design with a cross-sectional approach was employed. The sample comprised 60 children receiving dental healthcare services at Puskesmas Palangga. The level of anxiety was measured using the Face Image Scale. The findings revealed differences in anxiety levels based on the age of the children. Toddlers and young children tended to exhibit higher levels of anxiety compared to adolescents. Additionally, there were gender differences in anxiety levels, with girls experiencing higher levels of anxiety than boys. The study also found variations in anxiety levels based on the type of dental healthcare service provided. Tooth extraction procedures resulted in higher levels of anxiety compared to premedication and apex resection services. In conclusion, these research findings highlight the importance of considering age, gender, and type of dental healthcare service in managing anxiety among children receiving dental healthcare. Therefore, efforts can be made to create a comfortable and supportive environment for children during their dental treatment